Amygdalar Metabolic Activity Independently Associates With Progression of Visceral Adiposity - Ishai, Amorina; Osborne, Michael T; Tung, Brian; Wang, Ying; Hammad, Basma; Patrich, Tomas; Oberfeld, Blake; Fayad, Zahi A; Giles, Jon T; Lo, Janet; Shin, Lisa M; Grinspoon, Steven K; et al. (The journal of clinical endocrinology and metabolism, 2019)
Abstract Context Epidemiologic data link psychological stress to adiposity. The underlying mechanisms remain uncertain. Objectives To test whether (i) higher activity of the amygdala, a neural center involved in the response to stress, associates with greater visceral adipose tissue (VAT) volumes and (ii) this association is mediated by increased bone marrow activity. Setting Massachusetts General Hospital, Boston, Massachusetts. Patients Two hundred forty-six patients without active oncologic, cardiovascular, or inflammatory disease who underwent clinical 18F-fluorodeoxyglucose positron emission tomography/computed tomography imaging were studied. VAT imaging was repeated ∼1 year later in 68 subjects. Design Metabolic activity of the amygdala (AmygA), hematopoietic tissue activity, and adiposity volumes were measured with validated methods. Main Outcome Measure The relationship between AmygA and baseline and follow-up VAT. Results AmygA associated with baseline body mass index (standardized β = 0.15; P = 0.01), VAT (0.19; P = 0.002), and VAT/subcutaneous adipose tissue ratio (0.20; P = 0.002), all remaining significant after adjustment for age and sex. AmygA also associated with bone marrow activity (0.15; P = 0.01), which in turn associated with VAT (0.34; P < 0.001). Furthermore, path analysis showed that 48% of the relationship between AmygA and baseline VAT was mediated by increased bone marrow activity (P = 0.007). Moreover, AmygA associated with achieved VAT after 1 year (P = 0.02) after adjusting for age, sex, and baseline VAT. Conclusions These results suggest a neurobiological pathway involving the amygdala and bone marrow linking psychosocial stress to adiposity in humans. Future studies should test whether targeting this mechanism attenuates adiposity and its complications. We demonstrated that higher stress-associated neural activity was associated with visceral adiposity through bone marrow activity, suggesting a role for stress-related inflammation in central obesity.